(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
The paper analyses how the ’ndrangheta achieved to take root in the extraction of porphyry in Trentino to then extent its influence to other economic sectors and to the democratic life of the small municipality of Lona-Lases, up to the highest political and institutional exponents in the province. The results of the analysis highlights how preexisting conditions enabled ’ndrangheta to settle its first organized group (the so called “locale”) in Trentino-Alto Adige: the weaknesses and distortions which have characterized this economic sector since its birth and during its rapid development and the presence of an extended grey area.